1580 Factors influencing the increase of concentration of airborne endotoxin, mouse and rat allergens in an animal facility. (24th April 2018) - Di Renzi, S; Chiominto, A; Marcelloni, AM; Melis, P; Massari, S; Riviello, MC; Wirz, A; Sisto, R; Paba, E; D'Ovidio, MC
Abstract : Introduction: Researchers and technicians who work with laboratory animals are exposed to animal allergens and endotoxin in the workplace. Inhalation of these bio-contaminants has been identified as a risk factor for respiratory and allergic diseases resulting in impaired lung function and laboratory animal allergy. The objective of this study was to assess the exposure to environmental endotoxin and rodent allergens to propose the control and preventive measures. Methods: This study was conducted in an animal research facility. Stationary inhalable dust samples were collected using airChek2000 pumps equipped with IOM sampler and glass filter for endotoxin detection (Kinetic LAL assay) and with closed cassette and MCE filter for rat and mouse allergens ELISA analysis. Data were analysed by means of the statistical software R; the influence of changing cages on environmental contamination was assessed by multivariate statistical approaches (mixed effect linear regression models). Results: The concentration of endotoxin during changing cages increases significantly on average by a factor 1.8 with respect to the levels before or after this task (p =0.0414). Moreover, the highest concentration of endotoxin was measured during the preparation of bedding and distribution of feed. The level of Mus m 1 allergen was the most represented (mean=7.4 ng/m 3, σ=16.5 ng/m 3 ). During the changing cages was found a significant increasing of Rat n 1 and Mus m 1; Rat n 1 was also found in mouse rooms showing a contamination probably transported by the operators themselves. Conclusion: The environmental monitoring represents a powerful tool for assessing the determinant factors influencing the increase of endotoxin and animal allergen concentrations as well as underline the role of workers as passive sources of allergens. Furthermore, the identification of exposure peaks may represent an important information for the evaluation of appropriate engineering and preventive control measures particularly for workers employed in specific working tasks.